SEXUAL VIOLENCE AGAINST WOMEN: A CRITICAL ANALYSIS OF THE CRIME OF RAPE AND THE PERSPECTIVE OF PATRIARKALISM IN THE CRIMINAL JUDICIAL SYSTEM - Ferreira Alves, Bianca; De Sousa Carrias, Rebeca (Revista Gênero e Interdisciplinaridade, 2022)
This article will address the crime of rape and the impact of patriarchal culture on our judicial system, discussing the historical aspects that involve sexual violence against women and institutions such as: family, church, school, and state. This work will also address the increase in the crime of rape in Brazil and its consequences for victims. The research has as research problem the following guiding question: Is the patriarchal criminal justice system silent in relation to women victims of sexual violence? The objective is to analyze the treatment that the criminal justice system offers to women victims of sexual violence due to rape. The method to be performed in this research is a literature review, with regard to the objectives is exploratory and with regard to the methodology, the approach is deductive.